Permeability to water and viability in heteromorphic color seeds of bowdichia virgilioides kunth - Silva, Raquel Gonçalves [UNESP]; de Santana, Denise Garcia; Guimarães, Cristiane Carvalho [UNESP]; da Silva, Edvaldo Aparecido Amaral [UNESP] (FapUNIFESP (SciELO), 2021)
– Species that produce seeds with a rigid integument represent a serious problem because their impermeable coat restricts the entry of water, which makes germination difficult. The heteromorphism of the integument in Bowdichia virgilioides causes water imbibition to vary substantially and, therefore, the objective of this work was to study the relation of seed coat color with permeability and viability in Bowdichia virgilioides. Seeds were separated into five different colors (yellowish-orange, orange, orange/reddish, reddish, and rusty red) and the following parameters were analyzed: water absorption, germination, mortality, viability, synchrony, and maximum potential of germination. The color was a determining factor for most of the evaluated parameters. The seeds with yellowish or orange/reddish coats tend to be little permeable to water while seeds with reddish or rusty red coats are highly permeable. The results indicated that seeds with reddish color had greater physiological potential indicating a probable relationship with the maturation point of the species. However, in the seeds of the species studied, irrespective of coloring, germination was late with low synchrony and low daily seed germination count, typical characteristics of dormancy.
Permeabilidade a água e viabilidade de sementes heteromórficas de bowdichia virgilioides kunth
Keywords: Germination; Seed coat; Water uptake